DP-900 : Microsoft Azure data fundamentals video course + practise questions. - Garg, Eshant (Packt Publishing, 2022)
Gain a solid understanding of relational data workloads and relational Azure data services such as comparing PaaS, IaaS, and SaaS models by taking up this certification course About This Video Explore the different types of NoSQL databases and implementation NoSQL on Azure platform Learn different relational databases and implementation on Azure (Azure SQL Database and Managed Instance) Prepare for DP-900 Certification exam by solving sample questions In Detail DP-900 course is a fundamental course of Azure Data. The best part of this course is that there is no expiry to this course and doesn't need recertification. You will identify basic management tasks for relational data including provisioning and deployment of relational data services and describing query techniques for data using SQL language. Another significant factor that all candidates should consider for the successful training of the DP-900 exam is the overview of the exam skills. Applicants with a better understanding of the exam topics and weighting of the exam domains can gain a general impression of the exam prior to their preparation. The domains include core data concepts; different approaches to work with relational data on Azure; approaches to work with non-relational data on Azure; and the description of an Azure analytics workload. You will also learn how to describe relational data workloads and relational Azure data services such as comparing PaaS, IaaS, and SaaS delivery models. Finally, you will learn data ingestion and processing on Azure and data visualization in Microsoft Power BI. By the end of this course, you will be able to crack the DP - 900 certification exams. Audience This course is for those who want to pass the Microsoft exam DP-900 and for those who want to enter Azure Cloud data-related profiles such as data engineer, data scientist, and data analyst.